PENGEMBANGAN SISTEM ABSENSI FINGERPRINT UNTUK LAB SISTEM CERDAS PENDIDIKAN TEKNIK INFORMATIKA UNIVERSITAS PENDIDIKAN GANESHA - I Made Gede Widi Okiana (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
Nowadays, Ganesha University of Education, especially the Department ofEducational Information Technology (PTI), is still using manual procedure of presence checking system. Data of students’ presence is still acquired through printed media containing columns of attendance for each course they should take at the moment. This condition allows data manipulations which cause data inaccuracy if appropriate monitoring act is not properly done. Based on those uprising problems, the development of Fingerprint Presence Checking System for Intelligent System Laboratory of Department of Educational Information Technology is needed. In conducting this study, fingerprint sensor technology was applied to presence checking system. Therefore, possibility of presence manipulation was eliminated since students’ fingerprint is a unique personal characteristic. This system was developed using Microsoft Visual Basic 6.0 in which PHP scripting was used as programming language with MySQL as its database management system. Microsoft Visual Basic 6.0 was used in developing desktop interface for students’ presence checking system. Meanwhile, PHP programming script was used in developing web-based application for data administration system. The developed system is capable of utilizing fingerprint as data source on fingerprint sensor which equipped with students’ fingerprint identification system. Therefore, when students are doing registration, this presence checking system may work well. Besides, this developed system is also capable of identifying students’ fingerprints on registration process, managing presence data, and summarizing presence data for reportage purposes. This system is highly hoped to ease up students’ presence management system in Intelligent System Laboratory of Department of EducationalInformation Technology (PTI) in the Faculty of Technics and Vocations Undiksha. Therefore, their presence data is accurate and reliable.